Health benefits versus economic costs: welfare analysis of energy conservation and emission reduction - Zhao, Hongkun; Chen, Zhuo; Feng, Nan (Frontiers in Public Health, 2025)
IntroductionA multidimensional and comprehensive evaluation of the impact of energy conservation and emission reduction (ECER) on residents’ health and welfare is conducive to resolving conflicts between economy and environment on a worldwide scale.MethodsBased on China’s ECER demonstration city policy, this paper uses a staggered difference-in-differences method to examine the impact of ECER on residents’ health and labor market performance, and conservatively estimates the welfare effect of ECER in conjunction with a theoretical model.ResultsThe results show that ECER significantly improves residents’ health, raises self-rated health (β = 0.06, p < 0.05, 95% CI = −0.17 to 0.13), reduces the probability of illness affecting work (β = −0.004, p < 0.05, 95% CI = −0.01 to 0.01), and lowers medical expenditures (β = −0.183, p < 0.05, 95% CI = −0.64 to 0.10). However, ECER negatively affects residents’ labor market performance, reducing employment status (β = −0.032, p < 0.10, 95% CI = −0.11 to 0.06) and wage (β = −0.055, p < 0.05, 95% CI = −0.23 to 0.00). Mechanism analysis suggests that ECER primarily improves health by reducing emissions of pollutants such as urban industrial wastewater, industrial sulphur dioxide, and industrial fumes and dust, and negatively influences labor market performance by promoting industrial restructuring. Heterogeneity analysis shows that there is a selection effect in the impacts, the health benefits and economic costs of ECER are mostly achieved and borne by groups in rural areas, non-provincial capitals, and those suffering from chronic diseases and not engaging in physical activity. Welfare analysis suggests that the health benefits of ECER result in higher welfare gains than the negative welfare impacts of its economic effects.ConclusionFuture policies should progressively move towards an integrated assessment of the costs and benefits of ECER, paying particular attention to welfare losses among groups that bear higher costs.